Studies of SomeTransition Metal Complexes with β-Hydroxy α-Naphthalidine Anthranilino Hydroxamic Acid - Brat Singh, Shiv; Nath Thakur, Shiva (Asian Journal of Chemistry, 2010)
A series of complexes of the type MLX3 [M = Co(II), Cu(II) and Ni(II), X = H2O, pyridine, and α , β or γ picolines] have been synthesized with the ligand β-hydroxy α-naphthalidine anthranilino hydroxamic acid, H2L. Characterization of the ligand as well as complexes have been done on the basis of elemental analysis, spectral studies and conductivity and magnetic susceptibility measurements. Ligand has been found to coordinate through two of its nitrogen and one oxygen atoms. The complexes are found to be octahedral, the remaining three coordination sites are satisfied by oxygen of H2O or nitrogen of nitrogen donors such as pyridine and α , β or γ picolines.